Pelaksanaan Program Rehabilitasi Dalam Meningkatkan Motivasi Menekuni Keterampilan Bagi Peserta Didik di UPT Rehabilitasi Sosial Tuna Susila Kota Kediri - IHA MASULIYAH (J+PLUS UNESA, 2016)
ABSTRACT THE IMPLEMENTATION OF THE PROGRAMME OF REHABILITATION IN IMPROVING THE MOTIVATION OF ACQUIRING SKILLS FOR LEARNERS IN A SOCIAL REHABILITATION UPT SLUTTISH KEDIRI The rehabilitation program is an activity that is systematically arranged and planned to recover and develop the ability of a person who experienced social dysfunction in order to perform their social function appropriately in society. The purpose of the implementation of the program of rehabilitation is to regain a sense of self-esteem, self confidence, willingness, ability, awareness and responsibility for future self, family, community or social environment. The purpose of this research was based on the formulation of a problem is to figure out the implementation of the rehabilitation program, constraints and supporting factor in the implementation of the rehabilitation program. In the implementation of the rehabilitation program, viewed from the specified indicators including: learners, learning resources, tutors, a place to learn, learning tools, learning fund, yeast study, learning activities program and learning outcomes. From these indicators, the researchers can see the implementation of the rehabilitation programs provided to students, so that the rehabilitation programs there can provide knowledge and insight to the students. This study used a qualitative approach. The subjects in this study include managers, instructors or social workers and students (WTS). Data collection techniques used were interviews, participant observation and documentation. The collected data were then analyzed by step data reduction, data display, as well as verification and summary. After that tested the value of truth with credibility, dependability, confirmability and transferability. The results of the study obtained three conclusions. First, the implementation of rehabilitation programs given by UPT to learners meets the procedures that have been determined and done goodly. The activity programs which is given by UPT provide many benefits. These programs such as: social guidance, mental guidance, physical assistance and guidance skills. Second, there are some cases that become the obstacles in the implementation of rehabilitation program in UPT. These problems are derived from the learners, age factor and physical condition, education factors, limited infrastructure facilities and the allocation of time. Third, supporting factor, in the implementation of rehabilitation programs supporting factors are the fund. Funds provided are funds used to improve and develop programs that exist in UPT, The funding comes from the government and the private sector , with the funds , the rehabilitation program can run well so that learners are motivated to always follow each programs activities in the institution. Keyword: Implementation of the Program of Rehabilitation, Motivation ABSTRAK PELAKSANAAN PROGRAM REHABILITASI DALAM MENINGKATKAN MOTIVASI MENEKUNI KETERAMPILAN BAGI PESERTA DIDIK DI UPT REHABILITASI SOSIAL TUNA SUSILA KOTA KEDIRI Program rehabilitasi merupakan suatu kegiatan yang disusun secara sistematis dan terencana untuk memulihkan dan mengembangkan kemampuan seseorang yang mengalami disfungsi sosial agar dapat melaksanakan fungsi sosialnya secara wajar didalam masyarakat. Tujuan dari pelaksanaan program rehabilitasi adalah untuk memulihkan kembali rasa harga diri, percaya diri, kemauan, kemampuan, kesadaran serta tanggungjawab terhadap masa depan diri, keluarga, masyarakat atau lingkungan sosialnya. Tujuan dari penelitian ini berdasarkan rumusan masalah yaitu untuk mengetahui pelaksanaan program rehabilitasi, kendala-kendala serta faktor pendukung dalam pelaksanaan program rehabilitasi. Dalam pelaksanaan program rehabilitasi, melihat dari indikator yang telah ditentukan diantaranya yaitu : warga belajar, sumber belajar, pamong belajar, tempat belajar, sarana belajar, dana belajar, ragi belajar, program kegiatan belajar dan hasil belajar. Dari indikator-indikator tersebut, maka peneliti dapat melihat pelaksanaan program rehabilitasi yang diberikan kepada peserta didik, sehingga program-program rehabilitasi yang ada dapat memberikan pengetahuan dan wawasan kepada peserta didik. Penelitian ini menggunakan pendekatan kualitatif.Subyek dalam penelitian ini yakni pengelola, instruktur atau pekerja sosial dan peserta didik (WTS). Teknik pengumpulan data yang digunakan adalah wawancara mendalam, observasi partisipan dan dokumentasi. Data yang terkumpul kemudian dianalisis dengan langkah reduksi data, display data, serta verifikasi dan simpulan. Setelah itu diuji nilai kebenarannya dengan kredibilitas, dependabilitas, konfirmabilitas dan transferabilitas. Hasil penelitian menunjukkan bahwa didapatkan tiga kesimpulan. Pertama, Dalam pelaksanaan program rehabilitasi yang diberikan oleh UPT kepada peserta didik telah memenuhi prosedur-prosedur yang telah ditentukan dan dilakukan dengan baik. Program-program kegiatan yang diberikan oleh UPT memberikan banyak manfaat. Program-program tersebut diantaranya yaitu: bimbingan sosial, bimbingan mental, bimbingan fisik, serta bimbingan keterampilan. Kedua, Ada beberapa yang menjadi kendala dalam pelaksanaan program rehabilitasi di UPT. Kendala-kendala tersebut berasal dari peserta didik, faktor usia dan kondisi fisik, faktor pendidikan, terbatasnya sarana prasarana dan alokasi waktu. Ketiga, faktor pendukung, dalam pelaksanaan program rehabilitasi yang menjadi faktor pendukung adalah dana. Dana yang diberikan adalah dana yang digunakan untukmeningkatkan dan mengembangkan program-program yang ada di UPT, dana tersebut berasal dari pemerintah dan pihak swasta, dengan adanya dana, maka program rehabilitasi dapat berjalan dengan baik sehingga peserta didik termotivasi untuk selalu mengikuti setiap program-program kegiatan yang ada dilembaga. Kata Kunci : Pelaksanaan Program Rehabilitasi, Motivasi